ANALYSIS OF DIVIDEND POLICY THROUGH THE DETERMINANTS OF MANAGERIAL OWNERSHIP - Siti Asih (Universitas Pamulang, 2021)
One of the factors that attracts investors is dividend policy. A good profit-sharing system reflects the strength of the business and a solid management system, allowing investment to come in. However, in its implementation, dividend policy is strongly influenced by the ownership structure and internal conditions of the company. Therefore, this study aims to analyze which factors have a high probability of dividend policy decisions in companies that are members of LQ-45. Fundamentally, this research is included in the quantitative category with regression analysis techniques. A total of 45 companies were selected selectively using judgment techniques. The findings from the analysis confirm that the profitability factor regressively has the best and most positive relationship. That is, dividend policy is very dependent on how much profit is earned. Meanwhile, the EVA and Cash Turnover factors proved quantitatively not to be a strong consideration factor in making and making dividend policy decisions. Likewise with managerial ownership, that companies incorporated in LQ-45 shares tend to be professional in determining dividend policy, so that the managerial structure aspect does not affect dividend policy. However, simultaneously all factors have a positive possibility in influencing dividend policy. This means that the existence of cash turnover, EPS, management ownership structure and EVA together contributes to the determination of dividend policy, but is not based on a partial perspective.Keywords: Management Ownership Structure, EPS, Cash Turnover, EVA, Dividend Policy